Reconnaissance of 2016 Central Italy Earthquake Sequence. Issue 4 (November 2018) - Stewart, Jonathan P.; Zimmaro, Paolo; Lanzo, Giuseppe; Mazzoni, Silvia; Ausilio, Ernesto; Aversa, Stefano; Bozzoni, Francesca; Cairo, Roberto; Capatti, Maria Chiara; Castiglia, Massimina; Chiabrando, Filiberto; Chiaradonna, Anna; et al.
The Central Italy earthquake sequence nominally began on 24 August 2016 with aM 6.1 event on a normal fault that produced devastating effects in the town of Amatrice and several nearby villages and hamlets. A major international response was undertaken to record the effects of this disaster, including surface faulting, ground motions, landslides, and damage patterns to structures. This work targeted the development of high-value case histories useful to future research. Subsequent events in October 2016 exacerbated the damage in previously affected areas and caused damage to new areas in the north, particularly the relatively large town of Norcia. Additional reconnaissance after aM 6.5 event on 30 October 2016 documented and mapped several large landslide features and increased damage states for structures in villages and hamlets throughout the region. This paper provides an overview of the reconnaissance activities undertaken to document and map these and other effects, and highlights valuable lessons learned regarding faulting and ground motions, engineering effects, and emergency response to this disaster.